TINDAK BAHASA TERAPIS DALAM INTERVENSI KLINIS PADA ANAK AUTIS - Prasetyoningsih, Luluk Sri Agus (LITERA, 2014)
This study aims to describe types, functions, and strategies of therapeutic language acts in clinical interventions on autistic children. It employed the qualitative approach using the clinical pragmatic design. The findings are as follows. First, clinical therapeutic interventions on autistic children use illocutionary acts in the forms of directive, assertive, and expressive acts. In general, they use simple utterance patterns. Second, therapeutic verbal acts have functions to command, invite, require, refuse, ask, agree, state, explain, compliment, thank God, and thank. Third, strategies of therapeutic language acts are in the form of direct utterance strategies by means of calling, giving directions, and using visual objects or models.